In-office laryngeal procedures (IOLP) in Canada: current safety practices and procedural care - Yael Bensoussan; Jennifer Anderson (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The advent of chip tip technology combined with advanced endoscopy has revolutionized the field of laryngology in the past decade. Procedures such as transnasal esophagoscopy, site-specific steroid injections, injection laryngoplasty and laryngeal laser treatment can now be performed in the office setting under local anaesthesia. Although In-Office Laryngeal Procedures (IOLPs) have become standard-of-care in many American and several Canadian centers, there are no guidelines regulating the practice of these procedures. The goal of this report was to evaluate the current method of IOLP delivery in Canada. Methods An electronic survey was dispersed to 22 practicing Canadian laryngologists to assess safety and procedural care measures undertaken when performing IOLP. The survey consisted of 37 questions divided into 6 categories; 1) Demographic data 2) Facilities 3) Staff/personnel 4) Patient screening/monitoring 5) Procedure and emergency equipment 6) Reporting of adverse events. Results Data was collected for 16/22 laryngologists (72.7% response rate). Only 1 respondent did not perform IOLP. All performed injection augmentation laryngoplasty. Most performed laryngeal biopsies, intramuscular injection and/or electromyography guided injection for the treatment of spasmodic dysphonia and glottic/subglottic steroid injections. Only 4 respondents performed in-office KTP laser. Significant variation was found in procedural processes including intra procedural monitoring, anticoagulation screening, access to emergency equipment and documentation. Conclusion Our survey demonstrates that the delivery of IOLP in Canada varies considerably. The construct of IOLP practice guidelines based on the evidence with consistent documentation would promote safe, efficient and quality care for patient with voice disorders.